Aspects of the symbiosis between corals and Spirobranchus gaymardi (Quatrefages, 1866) (Polychaeta, Serpulidae) - Montebon, Augustus Rex F.; Yap, Maria Helena T. (Quezon City Marine Science Institute, College of Science, University of the Philippines Diliman, 2009)
Symbiosis, recently considered as the parasitism-commensalism-mutualism continuum, is pervasive in ecosystems like coral reefs. Spirobranchus gaymardi, also known as Christmas tree worms, are among the conspicuous symbionts of reef corals, fascinating both scientists and casual observers with their varied and lively colors and unusual habit. The dearth of information on Christmas tree worms, especially ecological studies in the country, encouraged the pursuit of the present research that tried to determine the natural distribution patterns of the sessile or adult forms of the worms, their larval dynamics, and the interaction of the adult worms with corals.
Thesis (Ph.D. Marine Science)--University of the Philippines Diliman
Keywords: Marine fauna -- Behavior; Symbiosis